A clinicopathological study of surgically resected lung cancer in patients with usual interstitial pneumonia. (August 2017) - Watanabe, Yasutaka; Kawabata, Yoshinori; Koyama, Nobuyuki; Ikeya, Tomohiko; Hoshi, Eishin; Takayanagi, Noboru; Koyama, Shinichiro
Abstract: Background: The clinicopathological characteristics of lung cancer with concomitant usual interstitial pneumonia (UIP) are insufficiently understood. This study aimed to elucidate a characteristic pathological feature of lung cancer that develops in patients with UIP, with a focus on the location of its onset. Methods: We reviewed surgically obtained specimens, including 547 tumors from 526 patients who underwent lobectomy for lung cancer. Surveyed patients were classified into three groups: patients with UIP (UIP group), patients with lung pathology other than UIP (non-UIP group), and patients without any associated lung pathology (normal group). The histology as well as the lobe and location of the onset of lung cancer were compared among these groups. The peripheral location was subdivided into subpleural, inner and tumor involved centrally secondary to extension. Results: The UIP group comprised 82 patients (male, 71 [87%]; mean age, 71 years; smoking rate, 94%), the non-UIP group comprised 334 patients (male, 267 [80%]; mean age, 69 years; smoking rate, 81%), and the normal group comprised 110 patients (male, 33 [30%]; mean age, 63; smoking rate, 29%). No statistical differences were noted in sex, mean age, or smoking index between the UIP and non-UIP groups. Compared with the non-UIP group, the frequency of squamous cell carcinoma (63% vs. 32%), lower lobe origin (76% vs. 32%), and subpleural location (24% vs. 5%) were significantly higher in the UIP group. Conclusions: Lung cancers in patients with UIP show a predilection for the subpleural region, where UIP is also thought to originate. Highlights: The frequency of histology of lung cancer with concomitant UIP was high in squamous cell carcinoma. The frequency of lung cancer with concomitant UIP was high in the lower lobe. A quarter of lung cancer cases with concomitant UIP develops in the subpleural regions where UIP similarly arises.